Enteral Tranexamic Acid Decreases Proteolytic Activity in the Heart in Acute Experimental Hemorrhagic Shock. (September 2019) - Aletti, Federico; Santamaria, Marco; Chin, Kevin; Mazor, Rafi; Kistler, Erik B.
The mechanisms for cardiac injury after hemorrhagic shock (HS) are unresolved. We hypothesize that remote organ damage can be caused by uncontrolled pancreatic proteolytic activity, as enteral protease inhibition improves outcomes in experimental HS. Uncontrolled proteolysis in the heart may disrupt cardiac metabolism and adrenergic control with subsequent deleterious outcomes. To test this hypothesis, the heart rate–pressure product (RPP) as an index of myocardial oxygen consumption and the levels of fatty acid transporter proteins CD36 and FATP6 as surrogates for metabolic activity in the heart were measured in rats subjected to experimental HS (n = 6/group) with and without the enteral protease inhibitor tranexamic acid (TXA). Plasma troponin I and heart fatty acid-binding protein (HFABP) concentrations were measured as indices of myocardial damage. Expression of the adrenergic receptors β1, α1D, and β2 was also measured in the heart to determine the possible effects of shock with and without enteral TXA on the adrenergic control of heart function. Hemorrhagic shock was induced by reduction in mean arterial blood pressure to 35 mm Hg for 2 hours before reperfusion of shed blood. The RPP was maintained in shocked animals treated enterally with TXA but not in those subjected to HS alone; this group also demonstrated decreased HFABP and plasma troponin I levels. Serine protease (trypsin, chymotrypsin, and elastase) and matrix metalloproteinase (MMP)-2 and MMP-9 activity was elevated in cardiac tissue and plasma after HS and abrogated by enteral TXA. Levels of CD36, FATP6, β1, α1D, and β2 were also increased after HS in cardiac tissue, and the increases were mitigated by TXA treatment. These results suggest that increased proteolytic activity may contribute to cardiac injury after HS. Enteral TXA prevents these changes, indicating a potential therapeutic option in the management of shock with resultant cardiac injury.